Acute promyelocytic leukaemia is characterized by stable incidence and improved survival that is restricted to patients managed in leukaemia referral centres: a pan‐Canadian epidemiological study. (30th April 2014) - Paulson, Kristjan; Serebrin, Anna; Lambert, Pascal; Bergeron, Julie; Everett, Janeve; Kew, Andrea; Jones, David; Mahmud, Salah; Meloche, Catherine; Sabloff, Mitchell; Sharif, Ismail; Storring, John; et al.
Summary Timely diagnosis and care are major determinants of the outcome in acute promyelocytic leukaemia (APL), a malignancy whose incidence may be increasing. The Canadian Cancer Registry (CCR) and health system represent valuable settings to study APL epidemiology. We analysed the CCR, which contains data on all Canadians with APL. To provide clinical information lacking in the CCR, we obtained data from five leukaemia referral centres during a similar time period. Between 1993 and 2007, there were 399 APL in Canada. Age‐standardized incidence was 0·083/100 000 and was stable over time. The early death (ED) rate was 21·8% (10·6% in patients <50 years old and 35·5% for those aged >50 years), with no improvement over time. Five‐year overall survival (OS) was 54·6% (73·3% in patients <50 years; 29·1% older patients). In the referral cohort, 131 patients were diagnosed between 1999 and 2010. ED was 14·6% and 2‐year OS was 76·5%. Within this cohort, ED and OS improved over time, although advanced patient age remained an adverse determinant of OS. In Canada, APL incidence is unexpectedly low and temporally stable. ED was higher than reported in clinical trials, but similar to reports from other registries. In contrast, ED was lower in referral centres and improved with time.